TEACHER PROFESSIONALISM AND LEARNING SERVICES TO IMPROVE STUDENTS’ LEARNING OUTCOMES IN PAI ELEMENTARY SCHOOL - Puspita, Arwini; Rezki, Reni; Hamid, Sundari; Hamsiah, A. (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2021)
Abstract: This study aims to observe the relationship between teacher professionalism and learning services, and students’ learning outcomes at PAI Elementary School. Population of this study was all teachers and students while the samples were 21 teachers and 30 students. The data collection used observation, interview, and documentation. The data analysis technique used is a descriptive analysis using SPSS 11.5, factor analysis, and Rank Spearman correlation analysis. The results show that: first, there is no significant relationship between teacher professionalism and students’ learning outcomes of PAI Elementary School. This is due to the lack of professional human resources within the scope of PAI Elementary School. Second, the learning services for PAI Elementary School students are in the high category, and there is a significant relationship between learning services and learning outcomes of PAI Elementary School students, this is due to the excellent service provided to the students so that it has an impact on the students’ learning outcomes. Abstrak: Tujuan penelitian ini adalah untuk mengetahui hubungan profesionalisme guru dan layanan pendidikan terhadap hasil belajar siswa sekolah dasar. Populasi dalam penelitian ini adalah guru dan peserta didik sekolah dasar PAI dan sampel sebanyak 21 orang guru dan 30 orang peserta didik . Pengambilan data yang digunakan adalah observasi, wawancara, dan dokumentasi. Teknik analisis data yang digunakan adalah analisis deskriptif dengan menggunakan SPSS 11,5, analisis factor, analisis korelasi Rank Spearman. Hasil penelitian: Pertama, tidak terdapat hubungan yang signifikan antara profesionalisme Guru dengan hasil belajar siswa Sekolah Dasar PAI. Hal ini disebabkan kurangnya SDM yang professional dalam lingkup Sekolah Dasar PAI. Kedua, pelayanan pembelajaran pada siswa Sekolah Dasar PAI berada pada kategori tinggi, dan ada hubungan yang signifikan antara pelayanan pembelajaran dengan hasil belajar siswa Sekolah Dasar PAI, hal ini disebabkan karena Pelayanan prima yang diberikan oleh pihak sekolah kepada siswa sehingga berdampak terhadap hasil belajar siswa.